2018
DOI: 10.1002/ajmg.a.38680
|View full text |Cite
|
Sign up to set email alerts
|

Worries and needs of adults and parents of adults with neurofibromatosis type 1

Abstract: Neurofibromatosis type 1 (NF1) is a neurocutaneous disorder associated with lifelong tumor growth propensity and neurocognitive impairments. Although follow‐up of adults with NF1 often focuses on tumor growth, follow‐up of cognitive or social problems and other NF1‐related comorbidity is often not a part of standardized care. In order to provide optimal care services for these patients, we explored the care needs of adults with NF1. A qualitative study was performed using semi‐structured group interviews, expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 56 publications
0
42
0
Order By: Relevance
“…Information and appropriate support in the work and living environment could alleviate the stress caused by limited independency. Additionally, peer groups can have a significant positive impact, as has been mentioned by youngsters with Neurofibromatosis Type 1 (Rietman et al 2018). Lastly, inclusion in appropriate physical activities will improve participation as well as physical and mental health.…”
Section: Activities and Participationmentioning
confidence: 94%
“…Information and appropriate support in the work and living environment could alleviate the stress caused by limited independency. Additionally, peer groups can have a significant positive impact, as has been mentioned by youngsters with Neurofibromatosis Type 1 (Rietman et al 2018). Lastly, inclusion in appropriate physical activities will improve participation as well as physical and mental health.…”
Section: Activities and Participationmentioning
confidence: 94%
“…Physical symptoms of NF1 and NF2 can interfere with typical patterns of communication (Arnold, Payne, Lorenzo, North, & Barton, 2018; Thompson, 2018). Difficulties with communication can negatively impact self‐esteem and quality of life, relationships among family and friends, the ability to adequately communicate particularly in public spaces, and the ability to perform appropriately at work and school (Cosetti, Golfinos, & Roland, 2015; Ferner et al., 2014; Rietman et al., 2018). Therefore, it is important to evaluate individuals with NF for possible communication challenges and refer appropriately for treatment.…”
Section: Genetic Counseling Processmentioning
confidence: 99%
“…Only one qualitative study of 30 adults with NF1 addressed the association between disease characteristics and the need for and received support (Rietman et al, 2018). Their findings suggested worries and needs for support in medical‐, mental health‐, and socioeconomic domains (including finances, relationships, and family planning) in young and adult persons with NF1 (Rietman et al, 2018). In our study, up to 20% of adults with NF1 reported a need for support, and adults with severe disease in particular experienced needs for physical, work‐related, and economic support.…”
Section: Discussionmentioning
confidence: 99%